2001
DOI: 10.1016/s0278-4343(00)00127-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient enrichment off Port Stephens: the role of the East Australian Current

Abstract: In January 1997, a bloom of the dinoflagellate Noctiluca scintillans occurred off Port Stephens, on the New South Wales (NSW) central coast. The nutrient enrichment that presumably caused the bloom was apparently unrelated to local winds. The purpose of this study is to investigate the role of the East Australian Current (EAC) in promoting nutrient-rich slope water into the euphotic zone off Port Stephens. To this end, a regional model of the NSW coast is presented and a new mechanism for upwelling is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 24 publications
2
66
0
Order By: Relevance
“…In contrast, waters of similar latitude on the Australian east coast are approximately twice as productive (Jitts 1965) and show a spring phytoplankton bloom with a second bloom in late summer to early autumn (Humphrey 1963, Hallegraeff & Jeffrey 1993. Sporadic increases in primary productivity on the southeast coast are the result of EAC activity that uplifts nutrient-rich slope water onto the shelf and close to the surface (Oke & Middleton 2001), sometimes in association with warm-core (Tranter et al 1986) or cold-core (Gibbs et al 1997) eddy formation, often resulting in coastal diatom blooms (Hallegraeff & Reid 1986 (Table 1). Analysis of silicate concentrations commenced in the 1970s.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, waters of similar latitude on the Australian east coast are approximately twice as productive (Jitts 1965) and show a spring phytoplankton bloom with a second bloom in late summer to early autumn (Humphrey 1963, Hallegraeff & Jeffrey 1993. Sporadic increases in primary productivity on the southeast coast are the result of EAC activity that uplifts nutrient-rich slope water onto the shelf and close to the surface (Oke & Middleton 2001), sometimes in association with warm-core (Tranter et al 1986) or cold-core (Gibbs et al 1997) eddy formation, often resulting in coastal diatom blooms (Hallegraeff & Reid 1986 (Table 1). Analysis of silicate concentrations commenced in the 1970s.…”
Section: Methodsmentioning
confidence: 98%
“…The intrusions of deeper water onto the shelf results from 4 different mechanisms: (1) wind-driven upwelling, (2) upwelling due to the EAC intruding onto the shelf, (3) acceleration of the EAC as the shelf narrows and (4) separation of the EAC from the coast (McLeanPadman & Padman 1991, Roughan & Middleton 2002. Frequently, upwelling occurs north of Port Hacking, often at ~31°S (Rochford 1975, Tranter et al 1986, Cresswell 1994, Gibbs et al 1997, Oke & Middleton 2001 and, as shown in the present study, the resulting phytoplankton bloom is subsurface by the time it arrives at Port Hacking (~34°S). These upwelling-favourable conditions are known to have a link with SOI atmospheric (Hsieh & Hamon 1991) and local weather conditions (McLean-Padman & Padman 1991).…”
Section: Port Hackingmentioning
confidence: 99%
“…First, the unidirectional East Australian Current (EAC) runs north to south along the east coast of Australia, and then weakens and deflects away from the coast at the south-eastern corner of the mainland (Knox 1963, Huyer et al 1988, O'Hara & Poore 2000, Oke & Middleton 2001, Roughan & Middleton 2004. Second, seawater and air temperatures decline with the transition from subtropical to temperate regions with increasing latitude.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…2b), and Port Stephens (PS, Fig. 2c), were chosen due to their predisposition to coastal upwelling (Rochford 1975;Hallegraeff and Jeffrey 1993;Oke and Middleton 2001), which is the dominant natural nutrient-enrichment process along the coast of NSW. There are no sewage outfalls within the immediate vicinity of the entrance of the estuaries in these regions.…”
Section: Methodsmentioning
confidence: 99%
“…Satellite images of sea surface temperature (SST) and sea surface Chl a (SeaWiFS) were obtained from the Commonwealth Scientific and Industrial Research Organisation (CSIRO) marine laboratories in Hobart. The general direction of flow of the East Australian Current was inferred from the SST images (Parslow et al 2000;Oke and Middleton 2001). However, current speed and direction along the coast were also measured 4 d after the November sampling run aboard the CSIRO research vessel, Franklin.…”
mentioning
confidence: 99%